Digi teacher / Inang Noor Liana Ibrahim and Khairul Intan Shahnaz Mohd Khalid - Ibrahim, Inang Noor Liana; Mohd Khalid, Khairul Intan Shahnaz (2002)
Digi teacher teaching aid is a very useful as teaching aid for the students of digital electronics. This report summarized the result and application of the ” Digi 1 eacher” study. Digi teacher application focuses on the certain outputs that can be obtained from certain inputs, after being through NOR gates and INVERTER (ICs). Study of ICs such as 7402 quadruple 2-mputs NOR-gates. 7404 Ilex Inverter and LED was made and evaluated. It can be improved by using rotary switch and three 7400 quad 2-input NAND gates ICs for better and easy handling for beginners